All The Best - The Star, (2008)
Federal Territories Minister Datuk Seri Zulhasnan Rafique handing over the contingent's flag to FT chef-do-mission Datuk Bakaruddin Othman for tje Sukma Gamer at Universiti Putra Malaysia yesterday. A total of 588 athletes and 175 officials will take part in all the events at the biennial Games in Kuala Terengganu from May 31-June 9.